The Efficacy of Applying the Repeated Reading Technique in Teaching Reading Comprehension - Eka Susilawati (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2022)
This classroom action research study investigates the efficacy of applying the repeated reading technique in enhancing reading comprehension among seventh-grade students at SMPS IT Al Izzah Sorong. The sample consists of 32 students, and the research design involves two cycles of interventions using a reading test comprising 20 multiple-choice questions as the primary instrument for data collection. The findings reveal a mean score of 70.85 in the pretest, indicating the baseline level of students' reading comprehension abilities. Following the implementation of the repeated reading technique, the posttest results show a notable improvement in students' comprehension levels, with a mean score of 79.62 in Cycle I and a further increase to 84.76 in Cycle II. The progressive trend in students' mean scores across the two cycles highlights the positive impact of the repeated reading technique on students' ability to comprehend and analyze descriptive texts. These results underscore the effectiveness of incorporating interactive and repetitive strategies in language arts instruction to support students' reading comprehension development. The study provides valuable insights into the benefits of utilizing the repeated reading technique as a pedagogical approach to enhance students' reading comprehension skills and promote academic success in language arts education.